Sustainable Energy Systems: Emerging Technologies and Practices in Renewable Energy Storage - Khalid, Muhammad (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
As climate change and environmental degradation worsen, renewable energy alternatives are more needed than ever. Addressing this worldwide issue brings difficulties and opportunities. Renewable technology has a major impact on the environment and climate change, presenting promise for lowering carbon emissions and global warming. Governments and organizations worldwide are creating renewable energy policies to expedite the transition to sustainable energy. This involves promoting a hydrogen economy, carbon accounting, and regional renewable installation laws. Solar, wind, biomass, and geothermal technologies are used to generate clean energy. EVs are helping renewable power systems peak-shave, load-follow, and build swappable storage stations. Advanced power electronic converters optimize renewable energy grid integration. Energy storage technologies including electrochemical, thermoelectric, and electromagnetic devices are improving renewable power system stability and resilience. Smart grids, microgrids, and machine learning are transforming renewable grids into more flexible, dependable, and self-healing ones. Renewable energy optimization, control, and forecasting are crucial for efficient energy generation and delivery. Renewable and distributed system planning, output power smoothing, and energy storage efficiency are crucial for the adoption of renewables. Load forecasting, demand response, and machine learning are changing renewable storage systems to improve power quality, grid stability, and renewable flexibility.